2012
DOI: 10.1007/s00701-012-1577-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteins involved in regulating bone invasion in skull base meningiomas

Abstract: BackgroundBone invasive skull base meningiomas are a subset of meningiomas that present a unique clinical challenge due to brain and neural structure involvement and limitations in complete surgical resection, resulting in higher recurrence and need for repeat surgery. To date, the pathogenesis of meningioma bone invasion has not been investigated. We investigated immunoexpression of proteins implicated in bone invasion in other tumor types to establish their involvement in meningioma bone invasion.MethodsRetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Local disease-related changes in bone erosion may also contribute to this effect. 21 Nonetheless, only a small absolute difference was found between the paraclinoid ICD in these patients compared with controls. Further investigation in a larger cohort of meningiomas is required to further elucidate the mechanisms by which ICD is affected.…”
Section: Discussionmentioning
confidence: 72%
“…Local disease-related changes in bone erosion may also contribute to this effect. 21 Nonetheless, only a small absolute difference was found between the paraclinoid ICD in these patients compared with controls. Further investigation in a larger cohort of meningiomas is required to further elucidate the mechanisms by which ICD is affected.…”
Section: Discussionmentioning
confidence: 72%
“… 4 These cases tend to be clinically challenging as complete tumor resection becomes more difficult and therefore the risk of recurrence increases. 5 It has been suggested that the molecular regulators of bone tropism in meningiomas may depend on their anatomical location as meningiomas of the anterior skull base show a distinct protein expression pattern compared with spheno-orbital meningiomas. 5 The most typical bony finding in meningiomas, however, is bone hyperostosis ( Fig.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed on 5μm thick tumor sections using heat-induced antigen retrieval method as described previously [ 43 ]. Briefly, slides were de-paraffinized in xylene for 30min followed by gradual hydration in decreasing concentrations of ethanol.…”
Section: Methodsmentioning
confidence: 99%